Aortocaval Fistula Unmasked: Spotting the Silent Threat in Emergency Vascular Imaging - Nurhamin Sofia Mohd Mustaffa; Muhammad Aminuddin Ashari; Mohd Noor Akmal Adam; Suhaila Bohan; Fang, Audrey Lee Suk (The Interventionalist Journal, 2025)
Aortocaval fistula (ACF) constitutes a rare but severe vascular complication of abdominal aortic aneurysm (AAA), characterized by the formation of an anomalous arteriovenous communication between the aorta and the inferior vena cava. This report presents the case of a 67-year-old male with underlying cardiovascular comorbidities who presented with progressive abdominal pain and hemodynamic compromise. Computed tomography angiography (CTA) revealed a large infrarenal AAA with synchronous contrast opacification of the aorta and inferior vena cava, consistent with an ACF. Definitive management via open surgical repair was undertaken, resulting in a favorable postoperative course. This case report aims to explore the various imaging modalities used in the detection of aortocaval fistula (ACF) and their clinical applicability. Among the available imaging modalities, CT angiography remains the gold standard due to its rapid acquisition, broad accessibility, and high sensitivity and specificity.